Edvard Munch: complete paintings : catalogue raisonné - Woll, Gerd (London, New York : Thames & Hudson, 2009)
A comprehensive study of Edvard Munch's paintings. It provides both scholars and collectors with a tool for further research and collecting.
v. 1. 1880-1897. Art dealership with cultural responsibility ; Munch's painted works / by Gerd Woll ; Chronology Edvard Munch 1863-1944 ; User's guide to the catalogue ; Catalogue nos. 1-414 -- v. 2. 1898-1908. Technical aspects of Edvard Munch's paintings / by Biljana Topalova-Casadiego ; Catalogue nos. 415-824 -- v. 3. 1909-1920. Munch's Aula paintings / by Petra Pettersen ; Catalogue nos. 825-1395 -- v. 4. 1921-1944. The many lives of Edvard Munch / by Patricia G. Berman ; Catalogue nos. 1396-1789 ; Appendix: Outline drawings and fragments, nos 1790-1871 ; Photographs and price list from Commetersche Kunsthandlung ; Exhibitions 1883-2007 ; Paintings in museums and public collections ; Painted portraits.
boek
Keywords: Munch, Edvard